Технології розвитку освіти - Лінькова, Олена Юріївна (ТОВ Видавництво "Точка", 2021)
Поширення діджиталізації процесів призводить до зміни технологій освіти. Основні вимоги до викладача: активація процесу самонавчання та співпраці; поширення роботи в команді; використання нових технологій.

The spread of digitalization of processes leads to changes in educational technologies. Basic requirements for the teacher: activation of the process of self-learning and cooperation; dissemination of teamwork; use of new technologies.
Keywords: технології освіти; діджиталізація процесів; інновації; дослідницька інфраструктура; компетентності; education technologies; process digitalization; innovations; research infrastructure; competencies